Effect of glucuronic acid on inducing self-assembly of Au nanoflowers@glucuronic acid on carbon cloth for non-enzymatic glucose sensing. (April 2023) - Yuwen, T.; Zou, H.; Xu, S.; Wu, C.; Peng, Q.; Shu, D.; Yang, X.; Wang, Y.; Yu, C.; Fan, J.; Zhang, Y.; Zang, G.
Abstract: Natural materials' structural variation boosts their performance. Therefore, the precise manipulation of the structure and properties of nanomaterials by self-assembly is a topic of great interest. Here, a self-assembly of glucuronic acid (GlcA)-coated Au nanoflowers (NFs) on flexible carbon cloth (SA-AuNFs@GlcA/CC) for non-enzyme electrochemical glucose detection was fabricated through the sequential deposition of gold and GlcA. The SA-AuNFs@GlcA/CC exhibits more highly exposed nanoedges than the normal AuNFs/CC without GlcA surface deposition, which may change the stereotyped traditional negative hypotheses of GlcA in glucose electrocatalysis. Notably, the unique 110 facets of Au atop the amino group grafted-CC were found in the SA-AuNFs@GlcA/CC, significantly improving the sensor's catalytic performance. The highly exposed nanoedges and unique 110 facets of SA-AuNFs@GlcA were systematically evaluated by scanning electron microscopy, transmission electron microscopy, and other electrochemical characterization tools. The SA-AuNFs@GlcA/CC exhibits excellent performance in glucose detection, including a wide linear range (5 μM-42 mM), a low limit of detection (5 μM, S/N = 3), high detection selectivity, good stability, and reproductivity. The sensor successfully detected glucose in human sweat samples and beverages in real time. Thus, this simple and green manufacturing method could be used as a novel strategy for glucose monitoring in biological and food samples. Graphical abstract: Image 1 Highlights: Use prepared, flexible SA-AuNFs@GlcA/CC as a nonenzymatic sensing platform for glucose measurement. A green, simple, self-assembly synthesis of Au nanoflowers on carbon cloth by glucuronic acid deposition is discussed. A novel procedure is proposed for fabricating Au nanoflowers enriched in 1 1 0 facets with high electrocatalytic activity. The fabricated sensor shows good performance for glucose monitoring in human sweat samples and beverages.